The Relationship between Emotional Intelligence, Self-Esteem, and Empathy among Nursing Students—A Pilot Study (Part 1) - Castelino, Patsey Sera; Mendonca, Theresa Leonilda (Journal of Health and Allied Sciences NU, 2023)
Objectives The aim of this study was to determine the relationship between emotional intelligence, self-esteem, and empathy of nursing students undergoing clinical experience in pediatric units.Materials and Methods A cross-sectional survey was conducted and data were gathered from 60 BSc nursing students undergoing clinical experience in pediatric units. Self-report questionnaires assessing emotional intelligence, self-esteem, and empathy were used and information about demographic details was collected.Statistical Analysis Pearson's correlation was used to find relationship between the constructs.Results Nursing students had moderately high level of emotional intelligence. Nursing students had below average level of empathy. There was no significant relationship between emotional intelligence and empathy of nursing students. There was a significant positive relationship between emotional intelligence and self-esteem of nursing students. There was no significant relationship between empathy and self-esteem of nursing students.Conclusion More research needs to be conducted to find the relationship between emotional intelligence, self-esteem, and empathy of nursing students so that proper training measures can be adopted to enhance these qualities which are crucial in providing quality care to the patients.
Keywords: emotional intelligence; empathy; nursing students; self-esteem